2014
DOI: 10.1073/pnas.1422488112
|View full text |Cite
|
Sign up to set email alerts
|

Treacher Collins syndrome TCOF1 protein cooperates with NBS1 in the DNA damage response

Abstract: The signal transduction pathway of the DNA damage response (DDR) is activated to maintain genomic integrity following DNA damage. The DDR promotes genomic integrity by regulating a large network of cellular activities that range from DNA replication and repair to transcription, RNA splicing, and metabolism. In this study we define an interaction between the DDR factor NBS1 and TCOF1, a nucleolar protein that regulates ribosomal DNA (rDNA) transcription and is mutated in Treacher Collins syndrome. We show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
122
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(133 citation statements)
references
References 29 publications
11
122
0
Order By: Relevance
“…Other identified nucleolar targets include the Pol I transcription termination factor TTF1 and a component of the early pre-rRNA processing machinery, UTP14A. Finally, Treacle-a factor implicated in transcription and rRNA modification and an interaction partner of Nijmegen breakage syndrome protein 1 (NBS1)-is also an ATM target (Ciccia et al 2014;Larsen et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other identified nucleolar targets include the Pol I transcription termination factor TTF1 and a component of the early pre-rRNA processing machinery, UTP14A. Finally, Treacle-a factor implicated in transcription and rRNA modification and an interaction partner of Nijmegen breakage syndrome protein 1 (NBS1)-is also an ATM target (Ciccia et al 2014;Larsen et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It should be pointed out, however, that similar experiments performed in human cells failed to show any inhibition of Pol I transcription following γ-irradiation (Moore et al 2011). More surprisingly, it has been demonstrated that laser microirradiation-induced DSBs outside of nucleoli lead to an ATM-dependent pan-nuclear silencing of Pol I transcription (Ciccia et al 2014;Larsen et al 2014). The difficulty in interpreting such experiments is that we have no knowledge of the number or distribution of DSBs.…”
mentioning
confidence: 99%
“…ATM is a key regulator for DSB-induced gene silencing in a mechanism involving H2A ubiquitination (15). ATM also represses Pol I-meditated transcription in the nucleolus (16,26,27), by a mechanism involving the interaction between NBS1 and Treacle protein (28,29). DNA-PK also induces gene silencing near DSB lesions (17), and a bromodomain protein ZMYND8 and the NuRD complex induce gene silencing at DSB sites (30).…”
Section: Discussionmentioning
confidence: 99%
“…It should be pointed out, however, that similar experiments performed in human cells failed to show any inhibition of Pol I transcription following γ-irradiation (Moore et al 2011). More surprisingly, it has been demonstrated that laser microirradiation-induced DSBs outside of nucleoli lead to an ATMdependent pan-nuclear silencing of Pol I transcription (Ciccia et al 2014;Larsen et al 2014). The difficulty in interpreting such experiments is that we have no knowledge of the number or distribution of irradiation-induced DSBs.…”
Section: Ganley 2005)mentioning
confidence: 99%